Study on AC-DC Electrical Conductivities in Warm Dense Matter Generated by Pulsed-power Discharge with Isochoric Vessel. (March 2016) - Sasaki, Toru; Ohuchi, Takumi; Takahashi, Takuya; Kawaguchi, Yoshinari; Saito, Hirotaka; Miki, Yasutoshi; Takahashi, Kazumasa; Kikuchi, Takashi; Aso, Tsukasa; Harada, Nob.
Abstract: To observe AC and DC electrical conductivity in warm dense matter (WDM), we have demonstrated to apply the spectroscopic ellipsometry for a pulsed-power discharge with isochoric vessel. At 10 μ s from the beginning of discharge, the generated parameters by using pulsed-power discharge with isochoric vessel are 0.1 ρ s ( ρ s : solid density) of density and 4000 K of temperature, respectively. The DC electrical conductivity for above parameters is estimated to be 10 4 S/m. In order to measure the AC electrical conductivity, we have developed a four-detector spectroscopic ellipsometer with a multichannel spectrometer. The multichannel spectrometer, in which consists of a 16-channel photodiode array, a two-stages voltage adder, and a flat diffraction grating, has 10 MHz of the frequency response with covered visible spectrum. For applying the four-detector spectroscopic ellipsometer, we observe the each observation signal evolves the polarized behavior compared to the ratio as I 1 / I 2 .